First Report of Goji Fruit Rot Caused by Aspergillus terreus in Ningxia, China - Zhou, Yueli (Plant disease, 2025)
Goji berry (Lycium barbarum L.) is a fruit with high nutritional and medicinal value, widely cultivated in northwest China (Wang et al. 2023). In June 2022, unusual lesion symptoms were observed on goji berries harvested from an orchard located in Yinchuan, Ningxia, China (38.65°N, 106.16°E), and stored for 3 days at 25 ± 2 ℃ and 50 - 60% relative humidity (RH). Approximately 82.86% of the goji berries (n = 251) showed rot symptoms, initially characterized by white hyphae and water-soaked lesions, which later became light yellow. These symptoms were accompanied by water loss, tissue collapse, and a foul odor. To isolate the pathogen, six symptomatic tissue pieces (2 to 3 mm2 each) excised from the lesion margins of goji berries were surface-sterilized with 75% ethanol for 30 s, rinsed three times with sterile water, treated with 0.1% HgCl2 for 30 s, rinsed three more times with sterile distilled water, and finally dried on sterile filter paper. The sterilized tissues were then placed on potato dextrose agar (PDA) plates and incubated at 28℃ in the dark for 5 days. The growing hyphae were transferred to new PDA plates using the hyphal tip method (Türkkan et al. 2022). Their fungal mycelium initially appeared white, gradually turned tawny and eventually became dark brown on PDA. The conidia were spherical, unicellular, smooth, pale yellow, and measured 2.05 ± 0.19 μm (n = 33). All morphological characteristics were consistent with Aspergillus spp (Dania and Olaleye. 2022; Embaby et al. 2022). The internal transcribed spacer region (ITS) of the ribosomal DNA, cis-aconitic acid decarboxylase (Cad), and β-tubulin genes of three representative isolates (LNB-2301 to LNB-2303) were amplified by PCR and sequenced using primers ITS1/ITS4, Cad-F/Cad-R, and T1/T2, respectively (Bafana et al. 2017; Glass and Donaldson 1995). The sequencing results of the three isolates were deposited in GenBank (OR701874, PQ789218, and PQ789219 for ITS; OR701875, PQ827464, and PQ827465 for β-tubulin; OR701876, PQ827462, and PQ827463 for Cad, respectively). BLASTn analysis of the ITS, β-tubulin and Cad sequences showed 99.65 to 100% sequence similarity with Aspergillus terreus. The phylogenetic tree analysis displayed that these new isolates (LNB-2301 to LNB-2303) clustered in the same clade with A.terreus C1. Pathogenicity tests were conducted three times by inoculating healthy fruits (n = 10) with 2 µL of conidial suspension (1x106 conidia/mL) from a 5-day-old culture of LNB-2301. Sterile distilled water was used as the negative control. All the inoculated fruits were incubated at 25 ± 2 ℃, 50 to 60 % RH. Symptoms after inoculation were similar to those observed on naturally infected fruits, whereas the control fruits remained asymptomatic as expected. Furthermore, the diameter of the lesions was 10.6 mm, as measured using the cross-bonded method on the fifth day. The pathogen was subsequently reisolated from these infected fruits and confirmed to be A.terreus based on the morphological characteristics and the molecular methods described above. To our knowledge, this is the first report of A.terreus causing postharvest goji berry decay